A checklist for readiness evaluation of Learning and Teaching area of AACSB standards. Issue 2 (7th November 2016) - Kundu, Goutam Kumar; Bairi, Jayachandra
Abstract : Purpose: The purpose of the paper is to introduce the concept of a checklist, focusing on the detailed analysis of requirements of the AACSB International – the Association to Advance Collegiate Schools of Business (AACSB) standards related to the learning and teaching area – for evaluation of implementation readiness in a business school setting. Design/methodology/approach: The present study adopted a multi-method approach for developing the final content of the checklist. Findings: The introduction of the checklist has provided a systemic approach to process design and evaluation of readiness of a business school for AACSB accreditation related to the learning and teaching area. The checklist was developed and applied over the course of systematic reviews in a business school setting. Research limitations/implications: The checklist has been developed considering the requirements of the AACSB standards related to the learning and teaching area only. In the near future, the authors intend to develop checklists for the remaining areas of AACSB standards. Originality/value: This research offers a comprehensive checklist comprising the requirements of the standards related to the learning and teaching area. The checklist would be useful to the business schools that are planning to implement AACSB standards for accreditation or are interested in changing their current processes to follow AACSB standards.